2019
DOI: 10.18203/issn.2454-2156.intjscirep20191859
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Apgar score with serum glucose, calcium and electrolytes on the asphyxiated neonates

Abstract: <p class="abstract"><strong>Background:</strong> Neonatal asphyxia is characterized by discrepancy of oxygen during perinatal period that can lead to severe hypoxic ischaemic organ damages followed by a fatal outcome including neurodegenerative diseases, mental retardation, and epilepsies. According to world health organization, four million neonatal deaths occurred each year due to birth asphyxia. Therefore, our study was designed to evaluate the status of serum glucose, calcium, electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
5
2
0
Order By: Relevance
“…A positive correlation was observed between the cord blood glucose concentrations and the 5-minute Apgar score among the cases (Table 3). These observations are consistent with Kavya et al [4], Basu et al [10], Sasidharan et al [13], Bahatkar et al [16], Islam et al [20], Joag et al [21], Rai et al [22], and Kumar et al [23].…”
Section: Discussionsupporting
confidence: 89%
“…A positive correlation was observed between the cord blood glucose concentrations and the 5-minute Apgar score among the cases (Table 3). These observations are consistent with Kavya et al [4], Basu et al [10], Sasidharan et al [13], Bahatkar et al [16], Islam et al [20], Joag et al [21], Rai et al [22], and Kumar et al [23].…”
Section: Discussionsupporting
confidence: 89%
“…Other authors [8,9,13,14] also found similar results with the present study. Similar to the current study, In Islam A et al [5]. and Kumar SD et al [4].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to calcium levels at 24-48 hours in the current study, Islam A et al [5]. and Kumar SD et al [4].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations